Identification of RUVBL2 as a novel biomarker to predict the prognosis and drug sensitivity in multiple myeloma based on ferroptosis genes - Sishi Tang; Xinyi Long; Fangfang Li; Siyi Jiang; Yunfeng Fu; Jing Liu (Hematology)
Background Multiple myeloma (MM) is a hematological malignancy with the proliferation of malignant plasma cells. Numerous studies have highlighted the critical role of ferroptosis in MM. However, how to use ferroptosis-related genes (FRGs) for prognostic prediction and treatment guidance in MM remains unknown.Methods By analysis of GEO databases, the prognostic gene was identified and a therapeutic strategy for MM patients based on FRGs was explored. A total of 12 FRGs were identified, utilizing the STRING database and Cytoscape software, and the PPI networks were constructed to identify hub genes and further functional enrichment analyses. Based on the aforementioned data, this study analyzed the expression of RUVBL2 in MM patients by qRT-PCR and Western blotting. To validate the functional role of RUVBL2 in the MM cells, cellular experiments were ultimately conducted.Results The analysis highlighted six hub genes, including TP53, MCM5, TLR4, RUVBL2, GCLM and ITGA6, and functional enrichment analyses indicating enrichment in DNA replication, regulation of apoptotic signaling pathway and PI3K/AKT signaling pathway. Prognostic analysis indicated that TP53, RUVBL2, and MCM5 are associated with MM prognosis, with RUVBL2 displaying a notable area under the curve (AUC) of 0.823 in ROC analysis. The study first determined that RUVBL2 is highly expressed in MM, siRUVBL2-mediated deletion of RUVBL2 inhibited proliferation, promoted apoptosis and increased the sensitivity of BTZ in MM cells, and also overcame BTZ resistance in CD138+ primary cells from MM patients.Conclusions Our study first suggested that RUVBL2 may be regarded as potential therapeutic targets and prognostic value in MM.